Risk Factors for Mortality From Late-Onset Sepsis Among Preterm Very-Low-Birthweight Infants: A Single-Center Cohort Study From Singapore - Goh, Guan Lin; Lim, Charis Shu En; Sultana, Rehena; De La Puerta, Rowena; Rajadurai, Victor Samuel; Yeo, Kee Thai (Frontiers in Pediatrics, 2022)
Objective To determine the risk factors for mortality associated with late onset sepsis (LOS) among preterm very-low-birthweight (VLBW) infants. Study Design We performed a retrospective cohort study of infants born <32 weeks gestation and <1,500 gm admitted to a Singaporean tertiary-level neonatal intensive care unit. We determined the clinical, microbial, and laboratory risk factors associated with mortality due to culture-positive LOS in this cohort. Results A total of 1,740 infants were admitted, of which 169 (9.7%) developed LOS and 27 (16%) died. Compared to survivors, those who died had lower birth gestational age (median 24 vs. 25 weeks, p = 0.02) and earlier LOS occurrence (median 10 vs. 17 days, p = 0.007). There was no difference in the incidence of meningitis (11.1 vs. 16.9%, p = 0.3), NEC (18.5 vs. 14.8%, p = 0.6), or intestinal surgery (18.5 vs. 23.3%, p = 0.6) among infants who died compared to survivors. Gram-negative bacteria accounted for 21/27 (77.8%) LOS-associated deaths and almost all (13/14, 93%) fulminant episodes. The presence of multiorgan failure, as evidenced by the need for mechanical ventilation (100 vs. 79.0%, p = 0.008), elevated lactate (12.4 vs. 2.1 mmol/L, p < 0.001), and inotropic support (92.6 vs. 37.5%, p < 0.001), was significantly associated with mortality. Infants who died had significantly lower white blood cell (WBC) counts (median 4.2 × 109/L vs. 9.9 × 109/L, p = 0.001), lower platelet count (median 40 × 109/L vs. 62 × 109/L, p = 0.01), and higher immature to total neutrophil (I: T) ratio (0.2 vs. 0.1, p = 0.002). Inotrope requirement [AOR 22.4 (95%CI 2.9, 103.7)], WBC <4 × 109/L [AOR 4.7 (1.7, 13.2)], and I: T ratio >0.3 [AOR 3.6 (1.3, 9.7)] were independently associated with LOS mortality. Conclusions In a setting with predominantly Gram-negative bacterial infections, the need for inotropic support, leukopenia, and elevated I: T ratio were significantly associated with LOS mortality among preterm VLBW infants.